Is the Price Right? The Role of Morals, Ideology, and Tradeoff Thinking in Explaining Reactions to Price Surges - Julio Elias; Nicola Lacetera; Mario Macis (Institute of Labor Economics (IZA), 2022)
Price surges often generate social disapproval and requests for regulation and price controls, but these interventions may cause inefficiencies and shortages. To study how individuals perceive and reason about sudden price increases for different products under different policy regimes, we conduct a survey experiment with Canadian and U.S. residents. Econometric and textual analyses indicate that prices are not seen just as signals of scarcity; they cause widespread opposition and strong and polarized moral reactions. However, acceptance of unregulated prices is higher when potential economic tradeoffs between unregulated and controlled prices are salient and when higher production costs contribute to the price increases. The salience of tradeoffs also reduces the polarization of moral judgments between supporters and opponents of unregulated pricing. In part, the acceptance of free price adjustments is driven by people's overall attitudes about the function of markets and the government in society. These findings are corroborated by a donation experiment, and they suggest that awareness of the causes and potential consequences of price increases may induce less extreme views about the role of market institutions in governing the economy.
Keywords: C91; D63; D91; I11; 330; price surges; price controls; preferences; morality; tradeoffs